2020
DOI: 10.3390/app10082984
|View full text |Cite
|
Sign up to set email alerts
|

Development of Computer-Aided Semi-Automatic Diagnosis System for Chronic Post-Stroke Aphasia Classification with Temporal and Parietal Lesions: A Pilot Study

Abstract: Survivors of either a hemorrhagic or ischemic stroke tend to acquire aphasia and experience spontaneous recovery during the first six months. Nevertheless, a considerable number of patients sustain aphasia and require speech and language therapy to overcome the difficulties. As a preliminary study, this article aims to distinguish aphasia caused from a temporoparietal lesion. Typically, temporal and parietal lesions cause Wernicke’s aphasia and Anomic aphasia. Differential diagnosis between Anomic and Wernicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The result of our study confirmed a study conducted by Silva et al (2020) that lesions in the temporal and parietal lobes are the underlying cause of anomic aphasia. Our research subjects who had anomic aphasia exhibited lesions in the temporal and parietal lobes.…”
Section: Lesion Locations In Patients With Anomic Aphasiasupporting
confidence: 91%
“…The result of our study confirmed a study conducted by Silva et al (2020) that lesions in the temporal and parietal lobes are the underlying cause of anomic aphasia. Our research subjects who had anomic aphasia exhibited lesions in the temporal and parietal lobes.…”
Section: Lesion Locations In Patients With Anomic Aphasiasupporting
confidence: 91%
“…In [4], the authors developed a system to classify Anomic and Wernicke's aphasia, based on the acoustic frequencies of speech signals. The system consisted of three diagnosis components-confrontation naming with 30 pictures to identify, single-word repetition of 15 single words, and comprehension components.…”
Section: Methodsmentioning
confidence: 99%
“…Aside from wearables, some systems can be utilized to potentially detect UCS. According to Silva et al [ 28 ], a system was developed to determine and differentiate subtypes of aphasia that occur due to a stroke. This classification method utilizes acoustic frequencies from pathological speech production and a comprehension analysis to distinguish various aphasia types.…”
Section: Related Workmentioning
confidence: 99%